ANALISIS MAKNA DAN FUNGSI KONFIKS PADA CERITA NOVEL YANG BERJUDUL LUKA SEMALAM - Simare Mare, Juni Agus; Siahaan, Delvina Yanti; Simorangkir, Chornelyus; Situmeang, Yusnita (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research aims to describe and explain the function and meaning of the confix in the story of the novel wound last night. The object of this research is a word that undergoes the affixation process, especially the confix. Data collection method with listen technique and note technique. The results of this study were analyzed descriptively with an interactive model. The results of this study are, there are several forms of words whose affixation is used, especially in the suffix ke-an, the suffix pe-an, the suffix ber-an, and the suffix se-an. The type of research used in this research is qualitative descriptive. That is a research method used to research on the natural condition of the object. Where researchers are one key instrument. Data collection techniques that are carried out using triangulation and combined methods. Data is collected by analysis and observation. From the results of this study, it shows that the meaning and function of the confix in the novel story of the last night there are 35 data that have the meaning of doing activities, expressing feelings, or stating circumstances, stating situations, expressing thoughts, stating places, expressing desires, expressing actions, and others. and the function of the suffix is as the formation of verbs, adjectives, nouns, and adverbs